Comparison of the Efficacy of Topical Clindamycin versus Niacinamide in the Treatment of Mild to Moderate Acne Vulgaris: a Systematic Review - Eden Leonita; Trisniartami Setyaningrum; Mohammad Fathul Qorib; Damayanti - (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Acne vulgaris (AV) is one of the most common skin diseases among teenagers and is treated based on its severity. Mild acne is treated with topical agents, while moderate and severe acne are treated with a combination of topical and systemic agents. Topical agents that are often used for acne are antibiotics, such as topical clindamycin. Widespread use of antibiotics to treat AV causes resistance problems. Therefore, alternative therapies are needed to prevent resistance to topical clindamycin, such as topical niacinamide, which has anti-inflammatory effects without inducing resistance problems. Purpose: To compare the efficacy of topical clindamycin and topical niacinamide in mild to moderate AV. Methods: In this systematic review, a literature search was carried out through 6 databases, following PRISMA 2020 guidelines. Inclusion criteria were written in English or Indonesian, published in 2010-2020, randomized controlled trial (RCT) study design, conducted on human samples, and discussed the efficacy comparison of topical clindamycin and niacinamide in mild to moderate AV. Studies that were not accessible in full-text and based on secondary data were excluded. Quality and risk of bias assessments were done using The Jadad Scale and Risk of Bias 2 (RoB 2). Result: Acne severity was reduced significantly in both topical clindamycin and niacinamide groups, and there was no efficacy difference between these groups. Both topical clindamycin and topical niacinamide can cause mild side effects. Conclusion: Topical niacinamide can be an alternative therapy to topical clindamycin because they are both effective in treating mild to moderate AV.